Middle East respiratory syndrome coronavirus (MERS-CoV) — Surveillance and testing in North England from 2012 to 2019. (April 2020) - Farooq, Hamzah Z.; Davies, Emma; Ahmad, Shazaad; Machin, Nicholas; Hesketh, Louise; Guiver, Malcolm; Turner, Andrew J.
Highlights: MERS is an emerging infectious disease with high consequences. PHE Manchester receives a high number of MERS surveillance samples. Sputum samples are the optimum samples for diagnosing respiratory viruses. Multiple samples per patient result in a 100% diagnostic yield and a confirmed end-diagnosis. Abstract: Background: Middle East respiratory syndrome coronavirus (MERS-CoV) emerged in Saudi Arabia in 2012 and caused an epidemic in the Middle East. Public Health England (PHE) Manchester is one of the two PHE centres in the UK that perform testing for MERS-CoV. The results of the PHE Manchester MERS surveillance from 2012 to 2019 are presented in this report. Methods: Retrospective data were collected for returning travellers from the Middle East fitting the PHE MERS case definition. Respiratory samples were tested for respiratory viruses and MERS-CoV using an in-house RT-PCR assay. Results: Four hundred and twenty-six (426) samples from 264 patients were tested for MERS Co-V and respiratory viruses. No MERS-CoV infections were identified by PCR. Fifty-six percent of samples were PCR positive for viral or bacterial pathogen with Influenza A as the predominant virus (44%). Sixty-two percent of all patients had a pathogen identified with the highest positivity from sputum samples. Patients with multiple samples demonstrated a 100% diagnostic yield. Conclusions: Although no cases of MERS were identified, the majority of patients had Influenza infection for which oseltamivir treatment was indicated and isolation warranted. Sputum samples were the most useful in diagnosing respiratory viruses with a 100% diagnostic yield from patients with multiple samples.